Photoisomerization behavior of photochromic amide-based azobenzene dyes exhibiting H-bonding effect: Synthesis and characterization - Hegde , Gurumurthy; Rajkumar, Yuvaraj Aralapura; Gan , Siew Mei; ., Syed Mahmood; Mandal, Uttam Kumar; Sudhakar, Achalkumar Ammathnadu (Springer, 2016)
Amide linkage was introduced into azo compound at para position and its optical storage properties were investigated. Synthesized compounds showed liquid crystalline behavior when electron withdrawing group was inserted in the chemical structure. UV/Vis study showed that the photoisomerization effect in solution occurred at 18-24 sec (E-Z) and 5-11 hours (Z-E), whereas in solids it occurred at 30 sec (E-Z) and 5 hours (Z-E). Photoisomerization effect of amide based azodyes in the presence of hydrogen bonding is discussed for the first time. Effect of terminal electronic withdrawing groups on hydrogen bonding is speculated to be the reason behind the surprising behavior. Strong evidence for the structure property relations reported here is useful for applications such as optical storage device in which one can tune the structure according to one’s requirement.